Source, occurrence, migration and potential environmental risk of microplastics in sewage sludge and during sludge amendment to soil - Gao, Ding; Li, Xin-yu; Liu, Hong-tao (The Science of the total environment, 2020)
Microplastics (MPs) are an emerging global pollutant. MPs research is mainly concentrated on water, with limited research on MPs in sewage sludge. MPs from various sources are collected into sewage and most of the MPs are trapped in the sludge during the sewage treatment process. Sludge is not only a sink of MPs, but also a source. Soil amendment with sludge provides nutrients into the soil, but it can also import substantial MPs into the soil, which has certain environmental risks. Therefore, we focused on the MPs in sludge and sludge-amended soil and conducted a literature review to summarize the sources, physical properties and fate of the MPs in sludge, as well as their separation, identification and statistical methods. MPs can accumulate in the soil, influence the properties of the soil, and also migrate, which might result in the pollution of deep soils and groundwater. In addition, the adsorption by MPs of heavy metals, organic pollutants, antibiotics and antibiotic resistance genes cannot be ignored as sewage sludge generally contains substantial concentrations of these pollutants. They can be adsorbed by the MPs and transferred into the soil with sludge amendment of soil. The combination and interaction of MPs with its adsorbed pollutants might increase environmental risk, further leading to possibility of them being uptaken by plants. The specific long-term risks to the environment caused by MPs in soil with sludge amendment require further exploration and investigation. [Display omitted] •60%–99% MPs from different sewage sources are detained in sludge.•Unified method for separation and statistical identification of sludge MPs required•MPs can adsorb heavy metals, organic pollutants, antibiotics and ARGs.•MPs in sludge have stronger ability to adsorb pollutants than original MPs.•Soil amendment with sludge containing MPs carries potential environmental risks.